A critical Analysis of factors working as impediments to “Meditation” inspite of wide acceptance as a mode of productivity Enhancement (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Although meditation is an effective tool  for increasing employee productivity, well being, and job satisfaction, research on the  effects of meditation on other corporate  factors such as presenteeism and emotional  intelligence is limited. The study looked  into the effects of meditation on awareness,  emotional understanding, job satisfaction, and  presenteeism in female corporate employees. The present study is focused on corporate  female employees to find out the barriers to  meditation. Researcher said that many do not  believe in meditation would help in anyways  reducing stress inspite of proven studies.  Few have no time to spend for meditation  though they don’t mind trying. Few have tried  meditation and was relaxing but still couldn’t  continue coz of stress or work load.  Understanding the practical challenges of  meditation and helping patients and clients  overcome those challenges will benefit from a  psychometrically valid measure of meditation  barriers. Finally, measuring meditation barriers is useful in both research and practice because  it aids in the identification of personal and  contextual variables related to meditation  barriers.
Keywords: challenges; practice; measuring